2021
DOI: 10.3390/jcm10204704
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnostic Imaging Study of Osteoradionecrosis of the Jaw: A Retrospective Study

Abstract: Radiation therapy (RT) plays a significant role in the management of head and neck malignancies. This study aimed to review the clinical symptoms and various imaging findings of osteoradionecrosis (ORN) and provide a clinical perspective on the development of ORN. The retrospective cohort was composed of 57 sites in 54 patients who had a history of RT and suspected ORN and 48 sites in 45 patients who were confirmed to have ORN. Image analyses included computed tomography (CT), magnetic resonance imaging (MRI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Diagnostic imaging studies revealed long-term RT-related bone marrow deterioration on MRI, and sclerotic changes in 82% of the bone marrow on CT. In the same study, PET/CT and SPECT were confirmed to be beneficial in the diagnosis of ORNJ, with PET/CT revealing the involvement of the tissue surrounding the affected bone and SPECT recognizing ORNJ' s tracer uptake (101).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Diagnostic imaging studies revealed long-term RT-related bone marrow deterioration on MRI, and sclerotic changes in 82% of the bone marrow on CT. In the same study, PET/CT and SPECT were confirmed to be beneficial in the diagnosis of ORNJ, with PET/CT revealing the involvement of the tissue surrounding the affected bone and SPECT recognizing ORNJ' s tracer uptake (101).…”
Section: Discussionmentioning
confidence: 67%
“…The ORNJ genesis process includes hypovascularization, hypoxia, and fibrosis that are brought on by abnormal bone marrow changes in addition to bone sclerosis brought on by RT-induced damage (7,44,88,101). Additionally, fibrosis and inflammation in the nearby masticatory muscles may cause one of the signs of ORNJ, trismus (111).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT imaging is indispensable for diagnosis and treatment planning for patients with ORN [ 5 , 15 ]. As irradiated bone is in a chronic inflammatory state, osteolysis, osteosclerosis, and sequestration are commonly observed [ 14 , 37 , 38 ]. Cortical disruption and/or disorganization of the trabeculation characterize osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosclerosis is characterized by increased bone density. Miyamoto et al described the mechanism by which radiation damage affects osteocytes and activates osteoblasts, leading to reactive bone consolidation, particularly in the cancellous bone area [ 38 ]. The inhibition and destruction of both osteoblastic and osteoclastic mechanisms also cause sequestration.…”
Section: Discussionmentioning
confidence: 99%